Avaliação da adição de montmorilonita organofilizada a adesivos baseados em borracha natural - Paim, Martina Fernandes (2016)
Adhesives, by definition, are substances capable of maintaining two materials together from the union of their surfaces. Due to the expansion of applications and variety of materials, adhesives are becoming important in several industrial fields requiring bonding reliability. Improvements in adhesives of natural rubber (NR) were achieved by adding a low level in the solid phase of organically modified montimorillonite (OMMT). The clay addition effect in elastomeric compounds was analyzed through the open time of adhesives, viscosity in rheoviscometer, curing behavior process by differential scanning calorimetry (DSC) and contact angle. Improvements in viscosity, open time and contact angle was observed in adhesives with nanoclay. The results group of these tests show that the improvement of the adhesive was more noticeable at a 4% OMMT adhesive due the lower contact angle and consequently better spreading. The curing behavior process showed no changes with OMMT incorporation.